The effect of electrification on socioeconomic well-being and environmental outcomes: Evidence for the Lao People's Democratic Republic - Ricardo M. Sousa; Phouphet Kyophilavong; Chowdhury Abdullah-Al-Baki; Mohammed Gazi Salah Uddin; Donghyun Park (Asian Development Bank (ADB), 2023)
We investigate the impact of electrification on the economic, educational, and environmental outcomes of the Lao People's Democratic Republic (Lao PDR). We use household-level data and a novel identification scheme, whereby we instrument the electrification status with the proportion of grid-connected households in a community. We find evidence consistent with the so-called "peer pressure for technology adoption," as a higher proportion of electrified households is linked with a boost in the electrification of neighboring households. Additionally, we find that electrification: (i) significantly increases income (in particular, farm income); (ii) improves children's educational completion; and (iii) reduces the use of dirty fuel for lighting and cooking. From a policy perspective, public investments and financial incentives for electricity generation and distribution can play a key role in alleviating the existing economic, educational, and environmental bottlenecks of developing countries like the Lao PDR.
Keywords: Q40; Q49; 330; electrification; household; fuel; income; education; Lao People's Democratic Republic